The Uniqueness of Endemic Animals Canary Crab (Birgus latro) as The Largest Crab Species in The Phylum Arthropoda - Krisdarwindah Mardiana; Andara Frida Sheilaliany Daely; Wahyu Irawati (Jurnal Biologi Tropis, 2023)
Birgus latro or walnut crab is the largest land arthropod animal in the world, this crab has a unique and complex anatomy and body morphology that supports its survival. The research objective was to describe the anatomy, morphology, habitat, behavior, role, nutrition, reproductive system, immune system, gas exchange system, blood circulation, digestive system, excretory system, and Birgus latro osmoregulation. The research method used is literature review. This type of research is a form of qualitative descriptive research with review techniques from research journals on Birgus latro in Indonesia. This research was conducted by analyzing the results of research that had been published nationally and internationally relating to the life of Birgus latro. Walnut crabs live in areas that are damp and dark and avoid the sun to reduce the occurrence of evaporation on their bodies. Hard body parts such as shells, claws, and skin contain lots of calcium and chitin for self- defense and climbing coconut trees. The circulatory system of the walnut crab is open, this crab is also an osmoregulatory animal. The advice that the author can give for the preservation of walnut crabs is to provide outreach to the community regarding the importance of maintaining and preserving the existence of walnut crabs which are almost extinct. Establishing a walnut shell conservation center must also be carried out by the government to maintain the coconut crab population, as well as cultivate walnut crabs with the right procedure.